Surgical management of urinary obstruction in young ruminants by tube cystotomy: A report of 24 cases - Kumar, Palli Ravi; Raghunath, Mjlinti; Sagar, Pentyla Vidya; Krishna, Nunna Veera Venkata Hari; Prasad, Vaddadi Devi; Sailaja, Bagadi; Baghyaraj, Devarapalli (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: To assess the efficacy of tube cystotomy along with medical dissolution of calaculi as a sole strategy for correction of obstructive urolithiasis in young ruminants. Materials and methods: Young bull calves (n=24; 10 Ongole claves and 14 Murrah buffalo calves) suffering from complete/partial urinary retention aging between 1 to 6 months were treated by tube cystotomy along with oral administration of ammonium chloride dosed at 10 gm/Kg body weight (bwt) orally for 15 days, streptopencillin dosed at 100 mg/10 Kg bwt through intramuscular (im) route for 5 days, and meloxicam dosed at 0.2 mg/Kg bwt through im route for 3 days. Results: Total 23 (95.83%) out of 24 calves started passing urine normally through the natural orifice 10-15 days postoperatively. None of the recovered animals (n=23) exhibited recurrence of symptoms, establishing the superiority of the technique in resolving the condition. Conclusion: Tube cystotomy, when performed at an early stage can prevent mortality of calves due to cystorrhexis, uroperitoneum and consequent uremia. This can avoid the painful and most tedious cysto-urethrotomy in young ruminants. http://doi.org/10.5455/javar.2016.c142